Liopropoma randalli, a new serranid (Teleostei: Perciformes) fish from the Indian Ocean - Akhilesh, K. V.; Bineesh, K. K.; White, William T. (Zootaxa, 2012)
A new serranid fish, Liopropoma randalli n. sp. is described from four specimens collected from the Indian Ocean offsouthwestern India and eastern Indonesia. It differs from all other species in the genus in its striking color pattern, a broadblack band from behind the eye to the caudal peduncle, semicircular dark-brown to black spots that cover the pink to red-dish body, and a combination of the following characters: 46 to 49 lateral line scales; 1–2 (4 as rudiments) + 12–13 (4–5as rudiments) gill rakers on the first arch (total 17–19); longest dorsal soft ray 2.1–2.3 in head length; 1st anal-fin spine10.4–12.2 in head length; 2nd anal-fin spine 4.4–4.9 in head length; pelvic fin relatively short, 5.1–5.7 in SL; and body depth 3.2–3.6 in SL.